2020
DOI: 10.1101/2020.08.03.20167403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mental health and experiences of discrimination of LGBTQ+ people during the COVID-19 pandemic: Initial findings from the Queerantine Study

Abstract: Objective: To assess mental health status and experiences of discrimination among a sample of Lesbian, Gay, Bisexual, Transgender, Queer people (LGBTQ+, the + including those who don't identify with any such label) during the COVID-19 pandemic. Design: Cross-sectional web-based survey. Setting: Responses were collected during the COVID-19 pandemic between April 27th and July 13th. Participants: 398 LGBTQ+ respondents forming an analytical sample of 310 in the main models. Methods: We used a combined measure of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
5
45
0
Order By: Relevance
“…Ten studies detailed SGM. [86][87][88][89][90][91][92][93][94] Most reported an increase in anxiety or depression during the pandemic. 86-92 94 A crosssectional observational quantitative study found an increase in experiences of mental distress, anxiety or depression among American SGM college students.…”
Section: Sexual and Gender Minoritiesmentioning
confidence: 99%
“…Ten studies detailed SGM. [86][87][88][89][90][91][92][93][94] Most reported an increase in anxiety or depression during the pandemic. 86-92 94 A crosssectional observational quantitative study found an increase in experiences of mental distress, anxiety or depression among American SGM college students.…”
Section: Sexual and Gender Minoritiesmentioning
confidence: 99%
“…Ignorance of marginalised groups of society aggravated their vulnerabilities and added miseries in their lives (Baker et al, 2020;Salerno, Williams et al, 2020). The LGBTQ+ community is prone to mental health issues and suffers from pre-existing health conditions such as anxiety and depression and social discrimination (Kneale & Bécares, 2020). The social distancing and stay at home policies decreased the social interactions and increased the anxiety level.…”
Section: The Lgbtq+ Community and Working-class Indian Gaysmentioning
confidence: 99%
“…Early findings from research on the effects of this suggests that women and children experiencing domestic abuse were particularly vulnerable (Green 2020). Some LBQTI people were forced to share households where their identities were at risk, for example when young people were forced to move back in with their parents (Kneale and Becares 2020).…”
Section: Householdsmentioning
confidence: 99%